Rasch analysis of the London Handicap Scale in stroke patients: a cross-sectional study - Park, Eun-Young (BioMed Central, 2014)
BACKGROUND: Although activity and participation are the target domains in stroke rehabilitation interventions, there is insufficient evidence available regarding the validity of participation measurement. The purpose of this study was to investigate the psychometric properties of the London Handicap Scale in community-dwelling stroke patients, using Rasch analysis. METHODS: Participants were 170 community-dwelling stroke survivors. The data were analyzed using Winsteps (version 3.62) with the Rasch model to determine the unidimensionality of item fit, the distribution of item difficulty, and the reliability and suitability of the rating process for the London Handicap Scale. RESULTS: Data of 16 participants did not fit the Rasch model and there were no misfitting items. The person separation value was 2.42, and the reliability was .85; furthermore, the rating process for the London Handicap Scale was found to be suitable for use with stroke patients. CONCLUSIONS: This was the first trial to investigate the psychometric properties of the London Handicap Scale using Rasch analysis; the results supported the suitability of this scale for use with stroke patients.